2018
DOI: 10.1002/jcp.26527
|View full text |Cite
|
Sign up to set email alerts
|

Whole body ARHGAP21 reduction improves glucose homeostasis in high‐fat diet obese mice

Abstract: GTPase activating proteins (GAPs) are ubiquitously expressed, and their role in cellular adhesion and membrane traffic processes have been well described. TBC1D1, which is a Rab-GAP, is necessary for adequate glucose uptake by muscle cells, whereas increased TCGAP, which is a Rho-GAP, decreases GLUT4 translocation, and consequently glucose uptake in adipocytes. Here, we assessed the possible involvement of ARHGAP21, a Rho-GAP protein, in glucose homeostasis. For this purpose, wild type mice and ARHGAP21 transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Besides, high glucose level stimulates the adaptive response of β-cell through insulin overproduction to compensate the IR. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…Besides, high glucose level stimulates the adaptive response of β-cell through insulin overproduction to compensate the IR. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that ARHGAP21 inhibition decreased body weight in mice (21), but the mechanisms involved remain unknown. It is well established that body weight and appetite control are complex and that central mechanistic disturbances can lead to hyperphagia or anorexia depending on the balance between the expression of anorexic and orexic genes in the hypothalamus (7, 28).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as expected, mice submitted to high-fat diet presented metabolic inflexibility. However, Het-HFD mice presented increased RER during the dark phase, suggesting an improvement in metabolic flexibility, which can be explained, at least in part, by increased insulin sensitivity (21) leading to efficient glucose uptake and oxidation. These data support the hypothesis that ARHGAP21 reduction is able to boost the nutrient handling, energetic homeostasis, and metabolic flexibility (42, 43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, investigating proteins and process that can mitigate beta cell overload and dysfunction may reveal new targets for better management of this pathology. In this context, our group has explored the role of ARGHAP21 (a RhoGAP protein), that has been implicated in cancer due to its suppressor tumor function, (4,5), and in the glycemic and insulin homeostasis (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%